2017
DOI: 10.1097/ta.0000000000001672
|View full text |Cite
|
Sign up to set email alerts
|

How does marijuana affect outcomes after trauma in ICU patients? A propensity-matched analysis

Abstract: Prognostic studies, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…7,8 Conversely, a recent statewide analysis demonstrated a pMS to be associated with decreased mortality in adult ICU trauma patients. 9 In support of this finding, multiple clinical studies have shown a pMS screen to have neuroprotective associations, including reduction of cognitive impairment and death following traumatic brain injury (TBI). [10][11][12] Therefore, we hypothesized a pMS to be associated with decreased mortality in all trauma patients, including ICU and younger adult (<40 years old) patient subset groups.…”
Section: Introductionmentioning
confidence: 95%
“…7,8 Conversely, a recent statewide analysis demonstrated a pMS to be associated with decreased mortality in adult ICU trauma patients. 9 In support of this finding, multiple clinical studies have shown a pMS screen to have neuroprotective associations, including reduction of cognitive impairment and death following traumatic brain injury (TBI). [10][11][12] Therefore, we hypothesized a pMS to be associated with decreased mortality in all trauma patients, including ICU and younger adult (<40 years old) patient subset groups.…”
Section: Introductionmentioning
confidence: 95%
“…reported “a positive marijuana screen is associated with decreased mortality in adult trauma patients admitted to the ICU” and may theoretically provide a neuroprotective effect in the setting of traumatic brain injury (TBI). [3] Abdel Fattah showed similar findings in their 2017 paper where cannabis users with severe injury did show an increased morbidity compared to nondrug users. [4]…”
Section: Discussionmentioning
confidence: 70%
“…3,16 Although Singer et al revealed reduced mortality in CB+ trauma patients admitted to the ICU, our study examined overall mortality of all CB+ and CB-trauma activations arriving in the ED and found no difference once controlling for differences in demographics and injury patterns in CB+ and CB-groups. 16 The strengths of our study include the size of the population used, the breadth of patient parameters collected, distribution data on the rates of cannabis associated traumas, chronological data of CB+ results, and the variety of the outcomes used. Weaknesses include the cannabis drug test itself and the potential confounding variable of tobacco smoking (data were not attainable for this retrospective study).…”
mentioning
confidence: 52%
“…In 2014, Nguyen et al found that cannabis was independently associated with survival after traumatic brain injury, and in 2017, Singer et al concluded that a positive screen was associated with decreased mortality in adult trauma patients admitted to the ICU. 15,16 However, potential protective effects of cannabis in trauma patients do not exist uniformly. Jehle et al found a significant increase in the proportion of burn patients who tested positive for cannabis, and those who tested positive had larger burns, longer length of stay, more days spent in the ICU, and a greater number of operations.…”
mentioning
confidence: 99%